Community Targeting of Uncontrolled Hypertension: Results of a Hypertension Screening and Education Intervention in Community Churches Serving Predominantly Racial/Ethnic Minority Populations. Issue 5 (September 2021) - Prendergast, Heather M.; Escobar-Schulz, Sandra; Del Rios, Marina; Petzel-Gimbar, Renee; McPherson, Charles; Jackson, Maya; Terrell, KaLynn; Heinert, Sara W.
Background. Uncontrolled hypertension is the primary risk factor for the development of cardiovascular complications and particularly burdens racial/ethnic minority populations. Aim. To determine the effectiveness of a community hypertension screening, education, and empowerment intervention on blood pressure (BP) improvement. Method . We screened 152 participants across four churches in predominantly racial/ethnic minority neighborhoods for elevated BP. During this visit, those with BP ≥ 140/90 mmHg were enrolled in the study and completed interventions. Individuals with moderately elevated BP (≥140/90 and <160/100 mmHg; Group 1) viewed a 3-minute hypertension education video. Individuals with severely elevated BP (≥160/100 mmHg; Group 2) additionally viewed echocardiograms images with subclinical changes from uncontrolled hypertension and had a brief on-site medication review with a pharmacist. Both groups received automated BP monitors and information on neighborhood federally qualified health centers for primary care. Participants returned to each church for follow-up 3 months later. We analyzed BP difference at 3 months and percentage with controlled BP for each group. Results . For Group 1, mean baseline and follow-up BPs were 143.5/88.0 mmHg and 138.5/85.8 mmHg, respectively. For Group 2, BPs significantly decreased from 165.4/98.3 mmHg to 150.4/90.8 mmHg. After the intervention, participants with controlled BP for Groups 1 and 2 were 35.5% and 55.2%, respectively. Discussion . Participants in both groups had BP improvements. Greater improvements were in individuals at higher cardiovascular risk due to severely elevated BPs (≥160/100 mmHg). Conclusion . This pilot highlights the impact that streamlined empowerment interventions with dedicated health personnel can have in high-risk communities with elevated BPs.